2022
DOI: 10.1097/dbp.0000000000001118
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Reading Aloud Beginning Prenatally and in Early Infancy: A Randomized Trial in Brazil

Abstract: Includes all participants contributing any data at baseline. a Comparison between randomization status (t test for continuous variables and x 2 for categorical variables).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…62 ► In Brazil, reading aloud to children beginning in pregnancy and early childhood was associated with increased vocabulary and reduced screen time, for families with low parent literacy. 63 ► In rural Vietnam, community-based, multicomponent group programmes for mothers and their infants 'Learning Clubs' improved early childhood development compared with the standardised mean. 64 ► A systematic review of physiotherapy in children with cerebral palsy showed that trunk-targeted exercises improve gross motor function, trunk control and balance, and help in greater functional recovery.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…62 ► In Brazil, reading aloud to children beginning in pregnancy and early childhood was associated with increased vocabulary and reduced screen time, for families with low parent literacy. 63 ► In rural Vietnam, community-based, multicomponent group programmes for mothers and their infants 'Learning Clubs' improved early childhood development compared with the standardised mean. 64 ► A systematic review of physiotherapy in children with cerebral palsy showed that trunk-targeted exercises improve gross motor function, trunk control and balance, and help in greater functional recovery.…”
Section: Reviewmentioning
confidence: 99%
“…In Brazil, reading aloud to children beginning in pregnancy and early childhood was associated with increased vocabulary and reduced screen time, for families with low parent literacy 63…”
mentioning
confidence: 99%
“…While poverty-related disparities in school readiness and academic achievement are multifactorial, cognitive stimulation has emerged as a primary target of many interventions aiming to enhance outcomes for children from low-SES backgrounds [17][18][19][20]. This is both because cognitive stimulation has been identified and highlighted as a positive experience in childhood that can buffer the negative consequences of poverty [15,21,22], and because it is demonstrated to be a modifiable factor [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%